FACILE ONE POT SYNTHESIS OF HIGHLY MONODISPERSE SILICA NANOPARTICLES IN WATER BASED MEDIUM - Oka Pradipta Arjasa; Jarot Raharjo (Jurnal Sains Materi Indonesia, 2012)
FACILE ONE POT SYNTHESIS OF HIGHLY MONODISPERSE SILICA NANOPARTICLES IN WATER BASED MEDIUM. Highlymonodisperse silica nanoparticles (SNs) were successfully prepared using water based synthesis. The right catalyst and controllable release of silanol compounds into water phase was the two mostimportant parameters in the SNs water based synthesis. The particle size of the SNs produced by this method was easily controlled by changing TetraEthyl OrthoSilicate (TEOS) concentration. The particle size ranging from 60 nm to 200 nm can be prepared in one pot synthesis. The SNs were analyzed by using dynamic light scattering.